Estabilidade e mudanças institucionais na indústria calçadista de Jaú/SP no período 1996-2016: auge e decadência econômica - Favoni, Celio (Universidade Federal de São Carlos, 2019)
The women's footwear industry in Jaú / SP has become a success story for many local development jobs in Brazil, provided by a set of institutions and organizations built specifically for and for this industry. With the implementation of the Brazilian Support Service for Micro and Small Enterprises (Sebrae de Bauru) in 1991, and mainly in 2001, with the signing of the Integrated Sectorial Program (PSI), APEX and Sebrae, to financial, technological, political and management resources that resulted in the increase of companies, production, employment and income. Within this context, the objective of this study was to show the stability and institutional changes in the women's footwear industry in Jaú, in order to explain the advances and setbacks during the years of greater activity (productive and organizational) that occurred between 1996 and 2016, in addition to identifying the institutional frameworks, the central actors and the factors that can explain the institutional environment of this locality. As a theoretical basis, we appropriate the lens of Institutional Theory, to understand organizational action and explain collective action, and Network Theory which is a way of thinking about social systems, focusing on the relations between the actors that make up the system, in their attributes and built ties. Among the forms of networks are the agglomerations of companies, often described as Local Productive Cluster (LPC), which showed evidence of forming cooperative ties, usually consisting of small and medium-sized enterprises. The study was structured in a documentary research based on institutional reports and secondary data from RAIS / MTE and Seade / SP. We used the UCINET 6.0 and Gephi® software for the construction of affiliation networks for the periods 1996/2001, 2002/2009 and 2010/2016. Field research was qualitative with the application of a questionnaire to nine central actors, between July 2017 and September 2018. The study pointed to two fundamental institutional milestones: for stability, which was the signature of the Integrated Sector Program (PSI) in 2001 and another for change, based on the Public Civil Action filed by the Labor Ministry against Sebrae in 2009. Regarding the networks, 99 actors were identified among entities, public bodies, individuals and companies that had some type of (Borgatti, Everett, Johnson; 2013) and showed structural changes in both the number of actors and the density. We also identified the central players, among them Sebrae and Sindicalçados, who played a fundamental role in the construction of the network and in the development of the sector, but had a reduction in their activities and influence after 2009. The results of the field research indicated difficulties in cooperation and the professionalization of the actors as the main problem, besides the absence of leaders, values or norms that could legitimize a habit of collective spirit or mutual aid that could be identified as a prerequisite of the process of institutionalization of a social group.
Stability and institutional changes in Jaú’s women’s footwear in the period 1996-2016: height and economic decadence
Keywords: Instituições; Redes; Calçados; Organizações; Institutions; Network; Footwear; Organizations; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::ECONOMIA REGIONAL E URBANA::ECONOMIA REGIONAL; ENGENHARIAS::ENGENHARIA DE PRODUCAO